Psychedelics and Psychotherapy: Cognitive-Behavioral Approaches as Default - Yaden, David B.; Earp, Dylan; Graziosi, Marianna; Friedman-Wheeler, Dara; Luoma, Jason B.; Johnson, Matthew W. (Frontiers in Psychology, 2022)
The acute subjective effects of psychedelics are responsive to users’ expectations and surroundings (i.e., “set and setting”). Accordingly, a great deal of thought has gone into designing the psychosocial context of psychedelic administration in clinical settings. But what theoretical paradigms inform these considerations about set and setting? Here, we describe several historical, sociological influences on current psychedelic administration in mainstream European and American clinical research settings, including: indigenous practices, new age spirituality from the 1960s, psychodynamic/psychoanalytic approaches, and cognitive-behavioral approaches. We consider each of these paradigms and determine that cognitive-behavioral therapies, including newer branches such as dialectical behavior therapy (DBT) and acceptance and commitment therapy (ACT), have the strongest rationale for psychedelic-assisted psychotherapy going forward. Our primary reasons for advocating for cognitive-behavioral approaches include, 1) they avoid issues of cultural insensitivity, 2) they make minimal speculative assumptions about the nature of the mind and reality, 3) they have the largest base of empirical support for their safety and effectiveness outside of psychedelic therapy. We then propose several concepts from cognitive-behavioral therapies such as CBT, DBT, and ACT that can usefully inform the preparation, session, and integration phases of psychedelic psychotherapy. Overall, while there are many sources from which psychedelic psychotherapy could draw, we argue that current gold-standard, evidence-based psychotherapeutic paradigms provide the best starting point in terms of safety and efficacy.